Teknik Flux Core Arc Welding Untuk Pria Kaum Bapa Elia Getsemani Paal IV Di Kelurahan Paal IV Kecamatan Tikala Manado - Lumintang, Romels; Mende, Jefferson; Ulaan, Tertius; Poeng, Rudy (Jurnal Poros Teknik Mesin UNSRAT, 2023)
The Community Partnership Program (PKM) is about training on the MIG Flux Core Arc Welding method for men of the fatherhood (PKB) Elia Getsemani Paal IV. This activity aims to provide training in non-gas MIG Flux core arc welding methods for men of the father Getsemani Paal IV to open up entrepreneurial opportunities and increase competitiveness when looking for work, The impact of this community partnership program for the men of Elijah Getsemani Paal IV can add participants' insights about work safety in welding work, welding methods, and joining techniques to the non-gas MIG Flux core arc welding method. Key words: PKB Elia Getsemani Paal IV, Flux Core Arc Welding